Nuclear Ribosomal DNA as a Probe for Genetic Variability in the Japanese Pear Pathotype of Alternaria alternata - Adachi, Yoshihiko (1993)
A restriction fragment length polymorphism analysis of nuclear ribosomal RNA genes (rDNA) was used to measure the amount and distribution of genetic variability in populations of the Japanese pear pathotype of Alternaria alternata on both micro- and macrogeographical scales. A total of 322 isolates were obtained from 13 areas in Aichi, Gifu, and Tottori Prefectures in central and western Japan. The restriction fragment length polymorphism analysis revealed that the pathogen populations contained at least eight rDNA variants. The eight variant types differed in the lengths and in the presence of the restriction sites in spacer DNA outside the coding regions for rRNAs. A total of 271 isolates were classified into the eight types. The remaining 51 isolates were determined to have mixed rDNA types. Single pear fields typically contained two to five types of rDNA variants. The frequencies of rDNA variants in 11 populations in Tottori Prefecture were compared; in this prefecture orchards containing the susceptible pear are common. Except for one collection site, there were no significant differences in the composition of the rDNA variants among the populations. This suggests that dispersal of inocula has occurred frequently in Tottori Prefecture. In contrast, significantly different distributions were observed in the three prefectures, indicating that gene flow between prefectures might be limited by geographical isolation. DNA fingerprints resulting from hybridization with a moderately repetitive DNA sequence of the fungus revealed greater genetic variability and geographical differences in genetic population structure even within the same rDNA type.